(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
After the independence of Uzbekistan, special attention was paid to the issue of objective and scientific study of the history of our country, and the attitude to the past has changed radically. Among a number of historical topics, special emphasis is placed on the hackneyed study of the history of the historically formed irrigation system and the culture of irrigated farming on the basis of a theoretical and conceptual approach. The study of the modern history of the water management system in Uzbekistan is of great importance today. This article analyzes and summarizes the history of the construction and development of canals and pumping stations in Uzbekistan.